What Pragmatism Was - Burke, F. Thomas, 1950- (American philosophy., 2013)
"Burke examines the philosophies of William James and Charles S. Peirce to determine how certain maxims of pragmatism originated. He contrasts pragmatism as a certain set of beliefs or actions with pragmatism as simply a methodology. He unravels the complex history of this philosophical tradition and discusses contemporary conceptions of pragmatism found in current U.S. political discourse and explains what this quintessentially American philosophy means today"--Back cover.